Ovarian Dysgerminoma: Unusual Presentation in Pregnancy with Acute Abdomen due to Internal Hemorrhage - Agrawal, Ajay; Rijal, P; Pokharel, H; Karki, S; Basnet, P; Dahal, P (Nepal Journal of Obstetrics and Gynaecology, 2013)
Dysgerminoma tends to occur in young women although its incidence in pregnancy is low. Torsion and incarceration occurs in nearly half of the cases. Early diagnosis and appropriate treatment offers the best prognosis to the patient presenting with dysgerminoma. However because of enlarging abdominal size, pregnancy may mask the rapidly growing dysgerminoma often leading to late presentation. This is a case report of a female 30 years of age with stage 3C dysgerminoma which lead to acute surgical abdomen at 33weeks of pregnancy. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 53-55 DOI: http://dx.doi.org/10.3126/njog.v7i1.8838